A social norms campaign based positive intervention aimed at promoting protective behaviours - Cuadrado, Esther; Arenas, Alicia; Tabernero, Carmen; Maldonado, Miguel A. (Frontiers in Public Health, 2024)
Social norms campaigns are communication strategies designed to influence people's behaviour by highlighting the social norms of their reference group. Such campaigns have been shown to be effective in promoting healthy behaviours in a variety of settings. This study explored the effectiveness of a social norms campaign applied to COVID-19 protective behaviours among university students during the pandemic. A total of 141 university students (83.1% female, 16.9% male) with a mean age of 21.55 years (SD = 4.33) initially took part in an experimental pre-test-post-test longitudinal panel study between January and July 2022, with participants randomly assigned to a control group (46 participants) or an experimental group (95 participants). Considering the experimental attrition, only 83 participants completed the last questionnaire (81.9% female, 18.1% male; mean age = 22.12 years, SD = 5.29), of whom 32 belonged to the control group and 51 to the experimental group. The results obtained using Student's t-test show that participants in the experimental group, who were exposed to the campaign, reported higher levels of self-efficacy, protective behavioural intention, and protective behaviours than the control group. It is concluded that social norms campaigns applied to COVID-19 protective behaviours are effective in times of pandemic and might be extrapolated to other epidemic contexts.